2015 10th International Conference on Broadband and Wireless Computing, Communication and Applications (BWCCA) 2015
DOI: 10.1109/bwcca.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Aware Migration and Replication of Processes in a Cluster

Abstract: Application processes have to be efficiently performed in presence of server faults in a cluster. Replicas of a process are performed on multiple servers to be tolerant of server faults. However, the more number of replicas of a process are performed, the more reliably and availably the process can be performed but the more amount of electric energy is consumed by servers. In this paper, we take a process migration approach to reliably and energy-efficiently performing process replicas. A process is replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We showed that no illegal information flow occur but about 10% to 20% of transactions are shown to be aborted in the RA-RBS and RA-OBS protocols. We are now discussing synchronization protocols to reduce the number of transactions to be aborted and to reduce the electric power consumption [18] of computer.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that no illegal information flow occur but about 10% to 20% of transactions are shown to be aborted in the RA-RBS and RA-OBS protocols. We are now discussing synchronization protocols to reduce the number of transactions to be aborted and to reduce the electric power consumption [18] of computer.…”
Section: Discussionmentioning
confidence: 99%
“…In [46], the process migration based on parameters decision and the system purpose, chooses one of four mechanisms: total copy, precopy, lazy copy, flushing, and designing the transfer process based on it. In [47], a migration mechanism is introduced based on a genetic algorithm that effectively mitigates the load imbalance in multiple processors. In this mechanism, the genetic algorithm is used to find the best destination for migrating the process.…”
Section: Process Migrationmentioning
confidence: 99%